Nested BIB designs, balanced bipartite weighing designs and rectangular designs - Sinha, Kishore; Mitra, Ranjit Kumar; Saha G.M. (Utilitas Mathematica)
The relationships between nested BIB designs, balanced bipartite weighing designs and rectangular designs are investigated. In the process some new balanced bipartite weighing designs and rectangular designs are obtained.